The Agricultural Credits Act of 1923 - Henderson, G. C. (Quarterly Journal of Economics, 1923)
Journal Article The Agricultural Credits Act of 1923 Get access G. C. Henderson G. C. Henderson Washington, D. C. Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 37, Issue 3, May 1923, Pages 518–522, https://doi.org/10.2307/1883853 Published: 01 May 1923